A visual study of the coanda effect on a circular wall water jet off-set from a smooth flat plate - Mahmoud, Samer Hassan (Kansas State University, 1996)
This work includes a visual study of the conda effects on the three dimensional laminar wall jet issuing from a circular opening parallel to a flat plate that is offset certain distance away from the nozzle center. The effect of varying the plate-to-nozzle distance on the laminar jet was investigated for five values of the plate-to-nozzle heights. It was verified as predicted by previous research that the point of the jet attachment to the wall moves away from the nozzle as the jet-to-nozzle distance increased. Also, the effect of the temperature variation between the jet and its surroundings were investigated qualitatively. The temperature difference between the jet and the surrounding was changed for a fixed nozzle-to-plate height. For the cold jet, at the low Reynolds Number, the jet remained detached from the plate. Some periodic instabilities were observed in the axial shape of the jet at distances further away from the nozzle. The effect of varying the flow rate on the jet were studied qualitatively. The jet axial and cross-sectional images obtained show how the jet shape changed with time. Simple two-dimensional theory was used to predict the attachment distance for the isothermal circular jet. No quantitative velocity profile measurements of the jet were undertaken in this study which was a preliminary investigation for building a scaled model for later studying of the air diffusion mechanisms of jet-wall interaction.